Antidiabetic and Hypolipidemic Potential of Cow’s Milk Yogurt with the Addition of Herbal Extracts in Diabetic Rats - Pazra, D. F.; Purwanti, M.; Handayani, K. S.; Wahyuningsih; Wahyuwardani, S. (Tropical Animal Science Journal, 2023)
Yogurt, with the addition of herbal ingredients can add efficacy and value of its benefits. Several studies have proven that cinnamon, aloe vera, and fenugreek seeds have properties as antidiabetic and hypolipidemic. The purpose of this study was to evaluate the antidiabetic and hypolipidemic potential of yogurt with the addition of a combination of two or three types of herbal extracts, such as cinnamon, fenugreek seeds, and aloe vera, in diabetic rats. Diabetic rats were divided into six groups and given treatment for 21 days. Rats’ blood was taken to test blood glucose levels using glucometers, insulin with the ELISA method, blood lipid profiles, and kidney and liver functions using a chemistry analyzer. The data were statistically analyzed using one-way ANOVA followed by the Duncan test. The results showed that yogurt added with several combinations of herbal extracts such as cinnamon, aloe vera, and fenugreek seeds (III, IV, V, and VI) could significantly reduce blood glucose levels, increase insulin levels, improve lipid profiles, and improve kidney and liver functions in diabetic rats, as well as commercial administration of glibenclamide (II). Diabetic rats given yogurt with the addition of a combination of 3 herbal extracts (VI) and a combination of 2 herbal extracts (cinnamon +fenugreek seeds) (V) of 1% each showed better antidiabetic and hypolipidemic performances compared to the other groups (III, and IV). The combination of yogurt with some herbal extracts can add efficacy and value to the benefits of yogurt as a functional drink.